Role of insurance in attracting FDI to Algeria - LALMI, FATIMA; SLIMANI, ILIES (My University, 2015)
This study has addressed the role of insurance in attracting and encouraging foreign direct investment in Algeria during the period (1970-2011) based on the standard model-based on the use of regression method of ordinary least squares (OLS) to estimate model parameters, a set of variables statutory function of insurance on foreign direct investment, and economic variables of the growth rate of real GDP, inflation rate, degree of economic openness, balance the general budget as a percentage of GDP, and the political changes of the degree of political stability. This study reached several conclusions are: there is one variable is linked to foreign direct investment relationship positive is insurance, while the rest of the variables are associated with the relationship of a negative, but it is there from his interpretation of significant and there are those who do not achieve this, it is through the test of significance parameters estimated can be accepted moral both hard and insurance and the rate of GDP growth and budget balance as a percentage of GDP and the degree of economic openness and the degree of political stability, and therefore are the explanatory variables for foreign direct investment by the estimated model.
Keywords: insurance, foreign direct investment, growth rate of real GDP, inflation rate, degree of economic openness, balance the general budget as a percentage of GDP, political changes of the degree of political stability.